The Analysis of Iranian EFL Learners' Acquisition of the American, British and Australian Accents - Pouriran, Ramin; Sajjadi, Samad; Pouriran, Khashayar; Sajjadi, Elaheh (Archives of Advances in Biosciences, 2016)
Farsi and English are both Indo-European languages with similarities in their roots. As such, this experiment was conducted to understand which English accent (i.e. American, British or Australian accents) would be easier for Iranians to adapt. To answer this question, 30 medical students performed three different activities of (I) listening to audio texts in three accents, (II) taking part in an oral interview and (III) completing an attitude questionnaire. The activities examined comprehensibility of the accents the participants were subjected to, type of accent they themselves produced and their attitude toward the accents under study. As for the audio texts, the order of presenting the three accents to the subjects was counterbalanced in order to control the order effect. The data on audio materials were analyzed for comprehensibility, accentedness, intelligibility and acceptability. Regarding comprehensibility, American accent was the most comprehensible (85%). Considering accentedness, intelligibility and acceptability, the participants found American accent the least accented (70%), the most intelligible 80% and the most acceptable (95%). In the interviews, students' accents were closer to the American accent. 85 percent of the participants used American accent in their conversational exchanges. Those with British and Australian accents formed 10% and 5% respectively. Regarding attitude, also, the participants mostly (90%) preferred American accent over the British or Australian accents. Students' tendency to adapt American accent more openly is mainly rooted in a mentality that American accent is easiest for the brain to digest.